2018
DOI: 10.1080/10810730.2018.1538272
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Examination of the Effectiveness of Framing Strategies to Reduce Mental Health Stigma

Abstract: This work was supported by Fonds Wetenschappelijk Onderzoek -Vlaanderen (FWO, ww.fwo.be/en/) under Grant FWO G070416N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Experimental research has demonstrated that the way in which issues are framed can influence the audience's attitudes (Lecheler & De Vreese, 2019). These effects extend to health-related topics -including dementia (e.g., Van Gorp et al, 2012), obesity (e.g., McGlynn, & McGlone, 2018 and mental illnesses (e.g., Vyncke & Van Gorp, 2018). This suggests that stigmatizing frames foster stigma, and as such, it is critical to dispel them.…”
Section: Theoretical Background Counterframing Strategiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Experimental research has demonstrated that the way in which issues are framed can influence the audience's attitudes (Lecheler & De Vreese, 2019). These effects extend to health-related topics -including dementia (e.g., Van Gorp et al, 2012), obesity (e.g., McGlynn, & McGlone, 2018 and mental illnesses (e.g., Vyncke & Van Gorp, 2018). This suggests that stigmatizing frames foster stigma, and as such, it is critical to dispel them.…”
Section: Theoretical Background Counterframing Strategiesmentioning
confidence: 99%
“…Stigma literature has presented redefinition as a possible way to reduce both stigma and internalized stigma, at least if this novel definition resonates with the public's preexisting attitudes and understanding of the world (Clair et al, 2016;Thoits, 2011). However, messages perceived as unpersuasive may unintentionally increase stigma (Chong & Druckman, 2007;Vyncke & Van Gorp, 2018). This risk may be reduced by using frames that contain a cultural element, such as references to myths or archetypes (Van Gorp et al, 2012).…”
Section: Theoretical Background Counterframing Strategiesmentioning
confidence: 99%
See 3 more Smart Citations